2014
DOI: 10.1162/jocn_a_00451
|View full text |Cite
|
Sign up to set email alerts
|

Face Familiarity Decisions Take 200 msec in the Human Brain: Electrophysiological Evidence from a Go/No-go Speeded Task

Abstract: Recognizing a familiar face rapidly is a fundamental human brain function. Here we used scalp EEG to determine the minimal time needed to classify a face as personally familiar or unfamiliar. Go (familiar) and no-go (unfamiliar) responses elicited clear differential waveforms from 210 msec onward, this difference being first observed at right occipito-temporal electrode sites. Similar but delayed (by about 40 msec) responses were observed when go response were required to the unfamiliar rather than familiar fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 79 publications
4
40
0
1
Order By: Relevance
“…The M240 deflection engages distributed anterior temporal cortices and may index familiarity detection and recognition, supporting previous iEEG findings (Barbeau et al, 2008). Furthermore, recent evidence shows that the (presumably analogous) N250 is sensitive not only to familiarity (Caharel et al, 2014), but that it emerges to previously unfamiliar faces as a result of repetition and, consequently, familiarization (Tanaka et al, 2006; Schweinberger et al, 2007; Pierce et al, 2011; Zimmermann and Eimer, 2013). Even though we did not manipulate repetition in a condition-specific manner, the present results are consistent with the idea that this deflection may reflect access to recognition units and activation of a memory trace for the particular face that has become familiar with repetition (Zimmermann and Eimer, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The M240 deflection engages distributed anterior temporal cortices and may index familiarity detection and recognition, supporting previous iEEG findings (Barbeau et al, 2008). Furthermore, recent evidence shows that the (presumably analogous) N250 is sensitive not only to familiarity (Caharel et al, 2014), but that it emerges to previously unfamiliar faces as a result of repetition and, consequently, familiarization (Tanaka et al, 2006; Schweinberger et al, 2007; Pierce et al, 2011; Zimmermann and Eimer, 2013). Even though we did not manipulate repetition in a condition-specific manner, the present results are consistent with the idea that this deflection may reflect access to recognition units and activation of a memory trace for the particular face that has become familiar with repetition (Zimmermann and Eimer, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Humans are capable of astonishing performances; for example, they can identify individuals despite not having seen them for decades (1) and can tell apart familiar from unfamiliar faces in a few hundred milliseconds (2,3). However, face recognition is one of the most difficult operations performed by the human brain: performance is highly variable across typical individuals (4,5) and can be severely disrupted following right occipitotemporal brain damage ("prosopagnosia") (6)(7)(8) or atypical development ("congenital/developmental prosopagnosia") (9,10).…”
mentioning
confidence: 99%
“…Moreover, social cues, such as eyegaze or head orientation, are processed faster when conveyed by familiar faces [14]. With a saccadic reaction paradigm, we found that participants were able to detect and shift their gaze to familiar faces in 180 ms [15] when the distractors were faces of strangers, a latency shorter a1111111111 a1111111111 a1111111111 a1111111111 a1111111111 than the known evoked potentials that differentiate familiar from stranger faces [16]; but see [17]). Overall, these results highlight a difference in processing between familiar and unfamiliar faces and point to a facilitation of familiar face processing that precedes the activation of a conscious, view-invariant representation [13,15], and that extends to the local features of a familiar face [12,14].…”
Section: Introductionmentioning
confidence: 77%